2016
DOI: 10.4103/1357-6283.178926
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting gender, evaluations, and examinations: Averting gender bias in an obstetrics and gynecology clerkship in the United States

Abstract: Medical student performance on the standardized national subject exam correlated with clinical evaluations independent of gender. Women had higher scores on both the subject examination and the clinical performance evaluations. There was no evidence of gender bias in the students' clinical evaluation scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our findings were similar to those of other studies in that scores generated from the tool across the APPE year were associated with APPE type, APPE block, GPA, student gender, and student age. [16][17][18][19][20][21][22] Similar to Fay's work, scores given by our faculty preceptors were lower than those given by non-faculty preceptors. 23 In our program, faculty members solely engage in delivery of either general medicine (27%) or ambulatory care (47%) APPEs, which could explain the finding that non-faculty community and institutional preceptors tended to score students higher.…”
Section: Discussionmentioning
confidence: 86%
“…Our findings were similar to those of other studies in that scores generated from the tool across the APPE year were associated with APPE type, APPE block, GPA, student gender, and student age. [16][17][18][19][20][21][22] Similar to Fay's work, scores given by our faculty preceptors were lower than those given by non-faculty preceptors. 23 In our program, faculty members solely engage in delivery of either general medicine (27%) or ambulatory care (47%) APPEs, which could explain the finding that non-faculty community and institutional preceptors tended to score students higher.…”
Section: Discussionmentioning
confidence: 86%
“…After reviewing the references of the included studies, we identified 5 additional articles that fulfilled our inclusion criteria, for a total of 32 articles included in our final analysis (Figure 1). 9,16–46 Additional details regarding each article are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…On a 9-point Likert scale, female students had a mean of 7.4AE0.9 (standard deviation) compared with 7.2AE1.0 for male students (P¼.001). 14 Coulson et al 15 did not identify gender differences in the clinical evaluation grade overall but did find differences in the components of the clinical evaluation. Eighteen full-time faculty members provided 545 evaluations of 101 third-year medical students on the obstetrics/gynecology clerkship and found that male faculty members were more likely to score male students higher on problem-solving (odds ratio, 1.7; 95% confidence interval, 1.0e2.7) and technical skills (odds ratio, 2.2; 95% confidence interval, 1.1e4.6) than female faculty grading the same cohort of male students.…”
Section: Clerkship Evaluation Performancementioning
confidence: 97%